New Species of Eupelte (Crustacea, Copepoda, Harpacticoida) from the East Sea, with Notes on the Zoogeography of the Genus - Sung Joon Song; Sang-kyu Lee (Journal of Marine Science and Engineering, 2024)
A new species of the genus Eupelte Claus, 1860, was obtained from the algal bed bottom in Dokdo Island, East Sea of Korea, using a light trap. Specimens of both sexes of the Korean new species are described in detail and compared with its congeners. The present species, Eupelte dokdoensis sp. nov., is closely similar to E. aurulenta Wells and Rao, 1987, found in algal sands from the Andaman and Nicobar Islands, and E. setacauda Monk, 1941, collected from seaweeds in the Californian coast of the USA. These species share the body length (0.5–07 mm), the nine-segmented A1, the setation of the first and second endopodal segments of P1 (one and four setae), P4 exp-3 with three inner setae, and enp-3 of P2–P4 with five setae in both sexes. The new species can be readily discernable from the previous two species by the short rostrum with a serrate distal margin, the shape of the maxillipedal basis, the setation and surface ornamentation of P1 enp-2 (covered with long setules), the exp-3 of P3 and P4 with thicker middle inner seta, and the setation of female and male P5 exopod and baseoendopod (six and six, four and two setae, respectively). In addition, the zoogeography of the valid species of the genus Eupelte is briefly discussed, and a diagnostic key to the females of the species is provided. Eupelte dokdoensis sp. nov. described herein is the first report of the genus from Korean waters and is the fourteenth member of the genus.